Pengaruh Jumlah Putus Benang Terhadap Quality Control Jahitan di CV Batara Apparel - Afriani Kusumadewi; Filly Pravitasari (Sainteks: Jurnal Sain dan Teknik, 2021)
One of the problems that related to quality and often occurs in the sewing process at CV Batara Apparel is that there are frequent thread break problems. Termination problems that occur are caused by an error during the thread installation process that does not pass through the needle bar hole and the thread is directly passed through the needle. This results in defects in stitches such as broken stitches. In order to solve the thread break problem caused by an error during the thread installation process that does not pass through the needle bar hole, it can be overcome by implementing SOP (Standard Operational Procedure) on proper and correct machine usage procedures, briefing supervisors with the production manager so that the problems occurs when production takes place can be handled properly. In addition, the implementation of regular maintenance schedules can also solve the thread break problems that occur. Keywords: thread break, loose stitches, quality control, SOP